Análise das transformações socioambientais com base em indicadores para recursos hídricos no cerrado baiano: O caso da Bacia hidrográfica do Rio de Ondas/BA. - Tomasoni, Marco Antonio (2008)
This work is an effort to understand the role of the different systems of the use of soil and its impact on the hidroambiental in the region of Cerrado. It builds on the benchmark theoretical and methodological state of the art in the development of studies with a focus on the issue of environmental indicators and their applicability as a parameter of decision-making for formulation and implementation of public policies, in this case with focus on the design of a model sustainability to the reality in the west of Bahia. The philosophical and conceptual dimension to the operational field, the use of environmental concepts, should be strict, focusing on finding pragmatic concrete possibilities interventions with answers measurable, in scenarios in several scales space-time, short, medium and long term. The various dimensions of what we call the environment requires efforts in several ways. Thus, trying to address problems concerning the environmental issue, the possibilities this problem, the conceptual discussion on terminology used in the issue of strategies for sustainable use of water resources, involving a general assessment, the models of management employees, experience in the area , The legal milestones in this process, the issue of the basin as the unit environmental strategic planning and intervention, the nature and context of implementation of the so-called environmental indicators and sustainability. This sequence of strategic approach is to elucidate the line of work that was undertaken research at some of the indicators of specific environmental and water resources, used by the management programmes at different levels of government, under the Catchment of Rio de Ondas in Barreiras-BA and make new ones generated in a position of control in the field, allowing scientifically assess impacts and environmental services, linking them with technical and soil management practices adopted by farmers in the west of Bahia.